2022
DOI: 10.1111/jgs.18068
|View full text |Cite
|
Sign up to set email alerts
|

Comparative risk of fracture in community‐dwelling older adults initiating suvorexant versus Z‐drugs: Results from LIFE study

Abstract: Background An increased risk of fracture has been reported in older adults taking hypnotics. However, few studies have reported the comparative safety of hypnotics with different mechanisms of action. We examined the risk of fracture in older adults initiating suvorexant compared to those initiating Z‐drugs. Methods We conducted a retrospective cohort study using a claims database within a longevity improvement and fair evidence (LIFE) study in Japan (1.5 million beneficiaries). People aged ≥65 years were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…A previous study reported a comparable risk of fractures between new users of suvorexant and Z‐drugs among community‐dwelling older people 8 . The results might have differed between the present study and the previous study, because inpatients with comorbidities experienced stronger adverse effects of Z‐drugs than did community‐dwelling outpatients.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…A previous study reported a comparable risk of fractures between new users of suvorexant and Z‐drugs among community‐dwelling older people 8 . The results might have differed between the present study and the previous study, because inpatients with comorbidities experienced stronger adverse effects of Z‐drugs than did community‐dwelling outpatients.…”
Section: Discussioncontrasting
confidence: 94%
“…A recent study using a claims database in Japan reported that new users of suvorexant among community-dwelling outpatients aged ≥65 years had a comparable risk of hip fracture or all-cause fracture compared with those who started Z-drugs. 8 In-hospital hip fractures lead to a higher mortality at 30 days and 1 year compared with those occurring in the community. 9 Therefore, it is important to clarify whether orexin receptor antagonists increase the risk of fractures among inpatients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this study is the first to compare suvorexant with BZRA sleep drugs. A similar study that compared Z-drugs with suvorexant showed no difference in fracture risk between suvorexant and Z-drugs [ 31 ]. Unlike our study, only Z-drugs were compared; therefore, a simple comparison cannot be made [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study that compared Z-drugs with suvorexant showed no difference in fracture risk between suvorexant and Z-drugs [ 31 ]. Unlike our study, only Z-drugs were compared; therefore, a simple comparison cannot be made [ 31 ]. In this study, suvorexant was prescribed more frequently than BZRAs to patients of advanced age and patients with physical comorbidities ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%